The determination of nucleotide arrangement in oligonucleotides derived from deoxyribonucleic acid : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University - Simes, Lynda Joy (Massey University, 1969)
The importance of DNA sequences The genetic material of all animals, plants bacteria, and of many animal and bacterial viruses has long been established as deoxyribonucleic acid or DNA, and recent studies (1a) have shown that its major function is to carry the genetic information required by a cell for the synthesis of species specific proteins. This information is stored by the nucleic acid macromolecule in the form of a linear code determined by its intrinsic nucleotide sequence or primary structure. The information is carried in such a way that a specific sequence of three nueleotides has the ability to code for one of every type of amino acid found in protein. In recent years the message corresponding to each nucleotide triplet has been established (2). Besides coding for amino acids, nucleotide sequences exist which are known to code for ribosomal transfer RNA's. There are probably other sequences which are involved in a variety of special roles, the more important being regulating and initiating transcription of the genetic message into functional messenger RNA, and the initiation of DNA replication. Because little information is available about the actual arrangement of bases needed to effect these functions, a knowledge of the complete nucleotide sequence of a biologically active DNA molecule may help to elucidate the nature of these extremely important processes. In addition it in hoped that new approaches can be found towards a better understanding of the actual changes to DNA caused by mutagens and carcinogenic agents, and it is also hoped that some knowledge can be obtained of the extent to which degenerate codons exist in genetic material, and the function of these codons when they do occur.
Keywords: DNA Analysis; Nucleotide sequence